Physical impairment aware scheduling in optical burst switched networks - Fan, Yuqi; Wang, Bin (Photonic network communications, 2009)
Optical burst switching (OBS) presents itself as a promising technology for bridging the gap between optical wavelength switching and optical packet switching. Increasingly, researchers attempt to incorporate more realistic constraints into the design of OBS networks. Optical signal transmission quality is subject to various types of physical impairment introduced by optical fibers, switching equipment, or other network components. The signal degradation due to physical impairments may be significant enough such that the bit-error rate of received signals is unacceptably high at the destination, rendering the signal not usable. In this paper, based on earlier work, we study the burst scheduling problem in OBS networks, taking into account physical impairment effects. We propose three effective burst scheduling algorithms: (1) a JET based Physical Impairment Constrained Algorithm (JETPIC), (2) an Integrated Physical Impairment Constrained Algorithm (IPIC), and (3) an Enhanced Integrated Physical Impairment Constrained Algorithm (EIPIC). At an OBS node, the proposed algorithms schedule bursts for transmission by searching for available resources as well as verifying signal quality. Our simulation results show that the proposed algorithms are effective in terms of reducing the burst blocking probability. In general, algorithm JETPIC outperforms algorithms IPIC and EIPIC in burst blocking probability and average end-to-end delay performance.